Forms and techniques of modern painting - Ning, Cui (Rhodes University, Faculty of Humanities, Department of Fine Art, 1999)
In this thesis, I have made an attempt to discuss and comment on oil painting from the "angle of concepts, forms, both traditional as well as more recent techniques of modern painting
Keywords: Painting, Modern